2019
DOI: 10.1111/1365-2745.13252
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in plant functional composition following long‐term drought in grasslands

Abstract: Plant traits can provide unique insights into plant performance at the community scale. Functional composition, defined by both functional diversity and community‐weighted trait means (CWMs), can affect the stability of above‐ground net primary production (ANPP) in response to climate extremes. Further complexity arises, however, when functional composition itself responds to environmental change. The duration of climate extremes, such as drought, is expected to increase with rising global temperatures; thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 106 publications
(178 reference statements)
7
130
1
Order By: Relevance
“…However, PD tempered the effect—with high PD, FD did not decrease resistance, suggesting an interplay between them such that both drive community assembly but with their impacts differing depending on each other. Griffin‐Nolan et al () showed a similar pattern, where changes in FD and PD did not consistently match; as functional traits changed from drought‐tolerance to drought‐avoidance, PD did not differ accordingly. Barber et al () showed that while PD did not change with environmental context, SD did respond to all the environmental gradients they analysed.…”
Section: Diversity Measures Give Different Complementary Informationmentioning
confidence: 95%
See 3 more Smart Citations
“…However, PD tempered the effect—with high PD, FD did not decrease resistance, suggesting an interplay between them such that both drive community assembly but with their impacts differing depending on each other. Griffin‐Nolan et al () showed a similar pattern, where changes in FD and PD did not consistently match; as functional traits changed from drought‐tolerance to drought‐avoidance, PD did not differ accordingly. Barber et al () showed that while PD did not change with environmental context, SD did respond to all the environmental gradients they analysed.…”
Section: Diversity Measures Give Different Complementary Informationmentioning
confidence: 95%
“…Barber et al () used 120 tallgrass prairie restorations to explore the PD and SD consequences of a variety of management and climatic variables in an uncontrolled field setting. Griffin‐Nolan et al () manipulated water availability to look at drought over 4 years while Miller et al () used a 19‐year time series to investigate the impacts of real droughts. Lastly, Cadotte et al () amassed results from 79 studies and 188 comparisons between FD and PD in a review that sought to glean generalities and insights into the relationship between FD and PD in studies across the globe.…”
Section: Measures Manipulations Of Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reordering may occur among species in similar or different functional groups (grasses, forbs, legumes) under ecological presses and pulses. Moreover, species within the same functional group can differ widely in their biotic interactions, traits, and influence on ecosystem processes (e.g., Magurran and Henderson, 2010; Griffin‐Nolan et al , 2019). For example, reordering of species led to changes in total above‐ground net primary production (ANPP) in a long‐term irrigation experiment (Collins et al , 2012; Knapp et al , 2012), and reordering was shown as the primary driver of community composition change across taxa in a long‐term observational study (Jones et al , 2017).…”
Section: Introductionmentioning
confidence: 99%